Correlation Between Reticulocyte Hemoglobin Equivalent (RetHe) With Erythrocyte Indices in Predialytic Chronic Kidney Disease Patients in Prof. Dr. I.G.N.G. Ngoerah General Hospital Denpasar - Christina Noviasiata Djawa; Sianny Herawati; Ni Kadek Mulyantari (Pharmacognosy Journal, 2023)
Background: Early detection and monitoring of anemia are important in CKD patients, which significantly increases the effectiveness of clinical treatment, reduce treatment cost and improve quality of life patients. Differential diagnosis of anemia based on conventional erythrocyte indices is limited, therefore it requires to be combined with other indices to determine iron deficiency. Reticulocyte hemoglobin equivalent (RET-He) is an alternative indicator of iron deficiency that is not affected by inflammation, and has been proposed as an additional marker for iron deficiency screening. Objective: To determine the correlation between RET-He and erythrocyte indices (MCV, MCH, MCHC) in predialytic CKD patients. Method: Cross-sectional retrospective study of predialytic CKD patient data in Prof. Ngoerah General Hospital, that were tested for RET-He and erythrocyte indices in January – March 2022. Data was collected from laboratory information system (LIS) and medical record. RET-He was measured with lightscatter flow cytometry method and erythrocyte indices was calculated. Result: Sixty and three (63) study subjects were consisted of 37 men (58,7%) and 26 women (41,3%), with average of age was 60,68±10,52 years. The mean value of RET-He, MCV, MCH and MCHC was 30,55±2,86 pg, 89,08±7,78 fL, 28,76±2,72 pg, and 30,55±2,86 g/dL. Result of data analysis showed positive correlation between RET-He and MCV (r = 0,659), MCH (r = 0,734), and also between RET-He and MCHC (r = 0,383), with p < 0,05. Conclusion: There was a significant positive correlation between RET-He with erythrocyte indices in predialytic CKD patients.
Keywords: Erythrocyte indices; Predialytic CKD; RET-He